2010
DOI: 10.1128/aem.02090-09
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Microsensor Measurement of Local Metabolic Activities in Ex Vivo Dental Biofilms Exposed to Sucrose and Treated with Chlorhexidine

Abstract: Dental biofilms are characterized by structural and functional heterogeneity. Due to bacterial metabolism, gradients develop and diverse ecological microniches exist. The aims of this study were (i) to determine the metabolic activity of microorganisms in naturally grown dental biofilms ex vivo by measuring dissolved oxygen (DO) and pH profiles with microelectrodes with high spatial resolution and (ii) to analyze the impact of an antimicrobial chlorhexidine (CHX) treatment on microbial physiology during stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 54 publications
(64 reference statements)
8
74
2
2
Order By: Relevance
“…These affected cells may have subsequently become detached from the biofilm base, an occurrence consistent with the observed reduction in biofilm thickness in the MT51 biofilms upon CHX treatment. These results are also in agreement with those of other studies (57)(58)(59) in which similar patterns of viability were observed in biofilm cells exposed to CHX. However, we did not see a complete eradication of the biofilms at either concentration of CHX (10 g ml Ϫ1 or 30 g ml…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These affected cells may have subsequently become detached from the biofilm base, an occurrence consistent with the observed reduction in biofilm thickness in the MT51 biofilms upon CHX treatment. These results are also in agreement with those of other studies (57)(58)(59) in which similar patterns of viability were observed in biofilm cells exposed to CHX. However, we did not see a complete eradication of the biofilms at either concentration of CHX (10 g ml Ϫ1 or 30 g ml…”
Section: Discussionsupporting
confidence: 93%
“…Since CHX effects include bacterial membrane damage (14,18,55), its bactericidal action can be measured using the BacLight LIVE/ DEAD stain (3,20,56,57), which is sensitive to the permeability of the cytoplasmic membrane. Upon CHX treatment, the percentage of viable cells, based on maintaining selective membrane permeability, decreased in both the WT15 and MT51 biofilms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The stained samples were then rinsed with PBS to remove excess stain and immediately imaged under CLSM. Live cells were stained green and dead and membrane compromised cells were stained red (von Ohle et al 2010). Confocal 3D stacks were taken on each of three independent replicate for the static, the shaking and microspray experiments in the same way as they were taken for the beads experiments (Supplemental material 1, Appendix Figure 1A-C).…”
Section: Antimicrobial Delivery and Killing Depth In The Biofilmmentioning
confidence: 99%
“…The addition of antiplaque agents or antimicrobials to toothpastes, mouthwashes and varnishes in order to kill bacteria is one of the most common ways to control oral diseases (Marsh 2006). The challenge, however, is that dental plaque bacteria organize themselves into biofilms, which increases their tolerance to these active agents through diffusion limitation (Stoodley et al 2008;von Ohle et al 2010). The role of the hydrodynamics in the enhancement of the delivery of active agents inside the biofilm has become a topic of interest, since it might also be utilized to improve delivery of dentifrices to oral surfaces (teeth, gums, tongue), or to bacteria directly.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, pH in dental biofilms was recorded with pH-sensitive electrodes that only allowed bulk pH measurements (22)(23)(24). The development of pH microelectrodes with tip diameters as small as 10 m (25) has improved the spatial resolution and made the recording of vertical pH gradients in dental biofilms possible (26,27). pH microelectrodes also are employed to measure pH z profiles in wastewater treatment biofilms, microbial fuel cells, and in the context of biocorrosion (28)(29)(30).…”
mentioning
confidence: 99%